Modeling Design of Ceramic Products Based on Digital Image Processing Technology - Lu, Yongqing (Mobile information systems, 2022)
With the improvement of people’s living standards, people’s pursuit of art is also getting higher and higher. Ceramic products are artistic works whose meanings contain thousands of stories including mountains, waters, and rivers. Ceramic products include vases, tea sets, flower pots, plates, and rice bowls. A vase is a vessel, mostly made of ceramic or glass, with a beautiful and smooth appearance. The bottom of the vase usually holds water, which keeps the plants alive and beautiful. Tea utensils refer to tea-drinking utensils such as tea cups, teapots, tea bowls, tea cups, saucers, and tea trays in a narrow sense. There are many kinds of tea sets in China, with beautiful shapes. In addition to practical value, they also have high artistic value, so they are well known at home and abroad and are favored by tea lovers in all dynasties. Digital image processing is the use of computers to remove noise and enhance, restore, segment, and extract features from images. Discrete mathematics is a mathematical subject that studies the structure of discrete quantities and their interrelationships and is an important branch of modern mathematics. The meaning of discrete refers to different elements connected together, mainly to study the structure and mutual relationship based on discrete quantities. Its objects are generally limited or countable elements. With the continuous development of digital image processing technology, this technology has also been applied to the shape design of ceramic products. This paper mainly conducts in-depth research on the preprocessing algorithm of digital images, from the initial analysis of the historical culture of the process to the subsequent algorithm research. Then its accuracy is matched to make a comparison, and finally an estimate based on the ceramics studied in this paper will be made. In the experimental part, the public is first investigated and analyzed, and the conclusion shows that the results of the color investigation of ceramic products include the following aspects: There are about 103 people having more needs for light and elegant color feeling, which echoes the needs of modeling. There are around 97 people demanding that the color be combined with the shape to reflect the color difference between the interior and the exterior. Since the internal and external chromatic aberration and mixed colors will bring novelty to the appearance of ceramic products, there are also a large number of people in the demand for mixed colors, about 84 people. Then it is analyzed that the ink-and-wash ceramics in the landscape style are more popular, and then the detailed description is carried out. Finally, the finished product is displayed.